Utilization Of Coconut Fiber Ash Waste As An Added Material In Mortar - Feriansyah Maulana Ahsan; Nurul Rochmah (Pusat Riset dan Inovasi Nasional, 2023)
Mortar is a mixture of materials composed of fine aggregate (sand), adhesives such as (clay, lime, portlaand cement) and water with a certain composition. Mortar can be affected by several specification factors such as density, mortar age, type of bonding material, and aggregate properties. In this study using coconut fiber ash as an added material in making mortar which has a function as an enhancer of compressive strength value in mortar. In coconut fiber ash, it has an important chemical compound for mortar, namely silica compounds which function as the main element to increase the compressive strength value of mortar. The purpose of the study was to determine the effect of adding coconut fiber ash material on the compressive strength of mortar with a percentage of 0%, 2.5%, 5%, 7.5%, 10%. From the results of the research conducted, a compressive strength value of 253 Mpa was obtained at a percentage of 10% of 7 days old and 253 Mpa at a percentage of 2.5% of 7 days old.